The next larger tenth is 76.1 .
The next smaller tenth is 75.9 .
Neither of those is any closer to 76 than 76 is.
76 is already rounded to the nearest tenth.
For this case, the first thing we must do is calculate the total cost.
We have then:
C = (16) * (2.4) * (6)
C = 230.4 $
Then, the change it receives is given by:
250 - 230.4 = 19.6 $
Answer:
He has received 19.6 $ from $ 250
Answer:
13) ⇒
15) ⇒
Step-by-step explanation:
Given expression:
13)
15)
Write the expressions in radical form.
Solution:
For an expression with exponents as fraction like
the numerator represents the power it is raised to and the denominator represents the nth root of the expression.
For an expression with exponents as negative fraction like
We take the reciprocal of the term by rule for negative exponents.
So it is written as:
using the above properties we can write the given expressions in radical form.
13)
⇒ [Using rule of negative exponents]
⇒ [writing in radical form]
15)
⇒ [Since 2nd root is given as in radical form]
-2 yo creo que está correcto